Public space and social protest in Colombia. Reflections during the Covid-19 pandemic - Martínez-Osorio, Pedro Arturo (Corporación Universitaria del Caribe, CECAR., 2021)
The situation in Colombia during the Covid-19 pandemic crisis, in the first months of 2021, where there were multiple demonstrations in public spaces against the government, a space that can be described as a macabre scenario of great uncertainty, leaves many questions about what those actions mean as a representation of Colombian society. Has the Colombian public space been vetoed as a necessary dialogue scenario in any democratic society?